The Influence Of Electronic Word Of Mouth, Price, And Brand Image On Consumer Buying Decision On Honda Hr-V Cars At Pt. Mandalatama Armada Motor Demak Branch - HARI DIFARANGGA AULIA SYAH PUTRA,; Bayu Kurniawan,; Rr. Hawik Ervina Indiworo, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to determine the Influence of Electronic Word Of Mouth, Price, and Brand Image on Consumer Buying Decisions on Honda HR-V Cars at PT. Mandalatama Armada Motor, Demak Branch. The population in this study were all car consumers at PT. Mandalatama Armada Motor, Demak Branch, this study used a probability sampling technique with a simple random sampling method using the Moe formula, a margin of error with a sample size of 98.01 and rounded up to 98 respondents. Data analysis in this study used multiple linear regression analysis using the SPSS version 24 program. The results of the analysis and discussion showed that partially Electronic Word Of Mouth had a positive and significant effect on Consumer Buying Decisions on Honda HR-V Cars at PT. Mandalatama Armada Motor, Demak Branch. Partially, Price has a positive and significant effect on Consumer Buying Decisions on Honda HR-V Cars at PT. Mandalatama Armada Motor, Demak Branch. Partially Brand Image has a positive and significant effect on Consumer Buying Decision on Honda HR-V Cars at PT. Mandalatama Armada Motor, Demak Branch